ПЛАНУВАННЯ ВУЗЬКОПОЛОСНОЇ PLC МЕРЕЖІ ДЛЯ СМАРТ ГРІД - Ямненко , Ю.С.; Осипенко , К.С.; Непорожнєв , І.В. (Інститут електродинаміки НАН України, Київ, 2012)
In the paper Smart Grid systems are investigated. Power Line Communication was used as communication technology for Smart Grid. System network planning and main steps of planning process were considered. On the stage of topological design Linear programming was used in order to solve equipment arrangement problem. Results for three different topographies: low, medium and mixed (low+medium voltage) are shown. At network realization Genetic algorithm was used energy-efficient control of electrical devices. References 7.